PENGGUNAAN METODE HYPNOTHERAPI UNTUK MENINGKATKAN KONSENTRASI SAAT START DALAM RENANG - Agus Supriyanto (Jorpres (Jurnal Olahraga Prestasi), 2016)
This study aims to increase the concentration of athletes at the start in swimming . The method in this study using action research  methods with training hypnotherapy . The subjects were 7 people swimming club coach coaches athletes as members of the PAB Pool DIY hypnotherapy to apply the method , and  the object of study is the BAO 25 athletes Pool DIY in 2010-2011 were subjected to hypnotherapy training model .Means of collecting data using instruments Grid Concentration Exercise to determine the level of concentration and test and measurement instruments to determine the ability of the swim start . The data  analysis technique used in this study is a descriptive analysis of the percentage .Based on the results of the reflection and discussion of action  research  above , it can be concluded  that  the method of  hypnotherapy can  increase the concentration of the athlete at the time of the start . In the first cycle , it is seen that the concentration of athletes is still low. In the second cycle of the general process of hypnotherapy can increase even though the increase  in the concentration of each individual is highly dependent on the tranquility of the sunounding environment readiness and suggestions athletes expected. Keywords : hypnotherapy , concentration , start in swimming